A expansão e interiorização da Universidade Federal de Uberlândia: um processo de democratização? - Padim, Dayton Fernando (2014)
The objective of this work to investigate an academic unit generated from a process of expansion of the federal universities, Faculdade de Ciências Integradas do Pontal (FACIP), located in Ituiutaba-MG and therefore outside the headquarters of the Universidade Federal de Uberlândia (UFU) . Aspects of daily life (practical, decision making) and the prospects for expansion, internalization and democratization, teachers, students and administrative staff were surveyed. The growing increase in enrollment in federal higher education began at the end of the first term of President Luiz Inácio Lula da Silva after decades of stagnation. In 2003, the Federal Government launched the Expand Programme, which was aimed to promote the internalization of public higher education, and thus have been the first step in the expansion and internalization of the Federal Higher Education Institutions (IFES). It was considered that this new model of educational institution needed to be analyzed in order to elucidate its rationality and oppose proclaimed goals and effectively targeted practices. In this sense, several theoretical frameworks, such as BOBBIO (1987), GAULEJAC (2007) and BOURDIEU (2004), guided the research. We understand that it is a broad subject, at each point analyzed was necessary to seek proper to perform the analysis theory. Data collection was through online questionnaires answered by teachers, students and administrative staff as well as through semi - structured interviews. Three teachers, two students, two technicians and two administrative political agents: Nine interviews with people, who participated and/or had information about the deployment process and development of the campus Depth, namely were performed. The content analysis of the interviews was done through reading, rereading, and construction and reconstruction of categories of analysis that allowed state inferences and interpretations. Three categories were created: Expansion and planning: implementation and conflict, development and organizational management, and Politics, and collegial decision-making processes organs. Were also searched and analyzed some official documents, the MEC and the UFU. Data analysis pointed to insufficient planning and subject to be developed even more problematic because of the power relations and restricted democratic character of decision-making processes. We conclude that only through processes more democratic decision, and when we say that we consider only the first step for the university break the walls that were built on decades of existence and open to the public that keeps, and is entitled a say in the direction that it believes is best for this area of intellectual, political and social education.